Polymeric Guide Conduits for Peripheral Nerve Tissue Engineering - Jiang, Huiquan; Qian, Yun; Fan, Cunyi; Ouyang, Yuanming (Frontiers in Bioengineering and Biotechnology, 2020)
Peripheral nerve injuries (PNIs) are usually caused by trauma, immune diseases, and genetic factors. Peripheral nerve injury (PNI) may lead to limb numbness, muscle atrophy, and loss of neurological function. Although an abundance of theories have been proposed, very few treatments can effectively lead to complete recovery of neurological function. Autologous nerve transplantation is currently the gold standard. Nevertheless, only 50% of all patients were successfully cured using this method. In addition, it causes inevitable damage to the donor site, and available donor sites in humans are very limited. Tissue engineering has become a research hotspot aimed at achieving a better therapeutic effect from peripheral nerve regeneration. Nerve guide conduits (NGCs) show great potential in the treatment of PNI. An increasing number of scaffold materials, including natural and synthetic polymers, have been applied to fabricate NGCs for peripheral nerve regeneration. This review focuses on recent nerve guide conduit (NGC) composite scaffold materials that are applied for nerve tissue engineering. Furthermore, the development tendency of NGCs and future areas of interest are comprehensively discussed.